A review on the environment-friendly emerging techniques for pretreatment of lignocellulosic biomass: Mechanistic insight and advancements. (February 2021) - Haldar, Dibyajyoti; Purkait, Mihir Kumar
Abstract: The process of pretreatment is considered as an indispensable unit operation in the field of lignocellulosic conversion. The traditional pretreatment operations of lignocellulosic biomass are observed as inefficient to meet the demand for an industrial adaptation. In view of that, numerous investigations are reported on various conventional pretreatment methods but very limited information's are available on the advanced technologies. The present review article provides an exclusive discussion on various emerging and environment-friendly pretreatment methods applied on a number of different feedstock materials. Further, an insight on the reaction mechanism involved with each of the technologies such as microwave, ultrasound, deep eutectic solvent, irradiation, and high force assisted pretreatment methods are elucidated for an effective valorization of lignocellulosic biomass. Hence, in a single article, the readers of this paper will get to know all important aspects of the emerging pretreatment techniques of lignocellulosic biomass including the advancements, and the mechanistic insight which will be highly beneficial towards the selection of an efficient pretreatment method for large scale of commercial implementation in a lignocellulosic biorefinery. Highlights: Several limitations of conventional pretreatment methods for lignocellulosic conversion are highlighted. Potential of emerging pretreatment methods for sustainable conversion of biomass is discussed. Insight on reaction mechanism involved with the emerging technologies is explored. Challenges and perspectives are summarized based on the futuristic approach.